Exploring quality of life and psychological distress in conjunctival tumor patients: An Indonesia cross-sectional study - Purnomo, Joko; Indrakila, Senyum; Soewoto, Widyanti; Malindha, Erma; Zulfan; Prastawa, Reza Pahlevi; Asmara, Yusuf Vindra (Faculty of Medicine, Universitas Islam Indonesia, 2025)
Background: Conjunctival tumor patients tend to exhibit a compromised health-related quality of life (HR-QoL) as a consequence of their condition.Objectives: To explore the quality-of-life (QoL) of conjunctival tumor patients and its association with psychological distress in Indonesia.Methods: A cross-sectional study with simple random sampling was used. Data collection occurred from May 9 to August 31, 2024. The health-related dimensions of quality of life were measured utilizing the reliable RAND SF-36, while psychological distress was assessed with the Hospital Anxiety and Depression Scale (HADS). We performed statistical analyses using version 26 of IBM SPSS, with normality assessed via skewness.Results: A total of 260 conjunctival tumors completed health assessments, revealing significant psychological distress and the RAND SF 36 questionnaire. The mean age was 51, 52.3% male, and 86.2% married. Participants had an average HADS anxiety score of 9.52, with 60.8% exhibiting anxiety, notably higher in those with malignant tumors (mean score: 10.64) compared to benign tumors (mean score: 8.57, p<0.001). Depression scores averaged 6.97, with 37.7% showing potential mild disorders. Health-related quality of life (HR-) was appraised across various domains, alongside overall physical functioning, averaging 60.76; benign patients scored significantly higher (71.95) than malignant patients (47.50). Correlations indicated that higher psychological distress negatively impacted QoL, with anxiety showing a strong correlation coefficient of -0.433 and depression at -0.306 (both p<0.001).Conclusion: Psychological distress is prevalent in conjunctival tumor patients, adversely affecting their QoL. These findings highlight the necessity of targeted interventions to enhance both physical fitness and mental wellness—challenges in this population. Further research is essential to develop effective support strategies tailored to their needs.